Enhanced Degradation of Norfloxacin Under Visible Light by S-Scheme Fe2O3/g–C3N4 Heterojunctions - Guang Lu; Wei Li; Zheng Li; Guizhou Gu; Qiuju Han; Jiling Liang; Zhen Chen (Molecules)
S-scheme Fe2O3/g–C3N4 heterojunctions were successfully fabricated by the ultrasonic assistance method to remove norfloxacin (NOR) under visible light irradiation. The synthesized catalysts were well studied through various techniques. The obtained Fe2O3/g–C3N4 heterojunctions exhibited an optimal photocatalytic degradation of 94.7% for NOR, which was 1.67 and 1.28 times higher than using Fe2O3 and g–C3N4 alone, respectively. In addition, the kinetic constant of NOR removal with Fe2O3/g–C3N4 composites was about 0.6631 h−1, and NOR photo-deegradation was still 86.7% after four cycles. The enhanced photocatalytic activity may be mainly attributed to the formation of S-scheme Fe2O3/g–C3N4 heterojunctions with built-in electric fields, which were beneficial to the separation and transfer of photostimulated charge carriers. Furthermore, a possible photo-degradation mechanism of NOR for S-scheme Fe2O3/g–C3N4 heterojunctions is described.